Sous vide processing to tenderise meat : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Food Technology at Massey University, Palmerston North, New Zealand - Akmal, Noorul Faridatul (Massey University, 2024)
The development of meat tenderness during sous vide cooking is associated with the proteolysis of meat proteins by endogenous enzymes, such as cathepsins B and L, and collagen solubilisation. However, these two processes are optimal at different temperature regimes. The aim of this thesis was to evaluate the effect of combining both temperature regimes through two-stage sous vide cooking on meat tenderness and cooking loss, as well as its ability to reduce total cooking time compared to conventional single-temperature sous vide cooking. This thesis also aimed to determine the roles of cathepsin B and L, collagen denaturation, and collagen solubilisation in the development of meat tenderness. Data for this thesis were obtained using beef pectoralis profundus (brisket), which is a tough meat cut that has the potential to gain tenderness through sous vide cooking. In this thesis, the kinetics of cathepsin B and L activity during sous vide cooking of beef brisket were evaluated at the temperatures of 46 – 60 °C for up to 72 h. Their activity initially increased, then decreased with longer cooking time. These changes in cathepsin B and L activity were successfully modeled using consecutive reactions in series, which are activation (the release of cathepsin from lysosomes) followed by deactivation (thermal denaturation). The model allows for the calculation of the cumulative activity of cathepsins for a given temperature and time. It was found that a greater cumulative activity can be achieved by sous vide cooking at lower temperatures such as 46 °C for a prolonged time compared to a higher temperature such as 56 °C. To evaluate the effect of precooking at different cumulative cathepsin B and L activities on meat tenderness, cooking loss, and collagen solubilisation, beef brisket was precooked at the temperatures of 46 °C and 56 °C for up to 72 h, followed by cooking at 71 °C. No change in the shear force value of meat precooked at 46 °C was observed, while a decrease in the shear force value was noted in meat precooked at 56 °C with increasing cooking time. Meat precooked at 56 °C also showed higher collagen solubilisation than meat precooked at 46 °C, while no difference in cooking loss was observed between the two precooking temperatures. From this work it was concluded that higher cumulative cathepsin B and L activity did not result in tenderisation of meat indicating that cathepsin B and L do not contribute to the development of tenderness in tough meat cuts like brisket. On the other hand, meat tenderness appears to be correlated with collagen solubilisation. A further study using precooking at different cumulative activities (46 – 56 °C for 0 – 12 h), followed by cooking at 80 °C for 8 h, supports the result that cathepsins B and L do not contribute to meat tenderisation during sous vide cooking. In this study, beef brisket precooked at 46, 50, and 53 °C for 12 h and at 56 °C for 6 and 12 h had a lower shear force value than meat cooked directly at 80 °C for 8 h. Faster tenderisation was observed as early as 6 h with precooking at 56 °C. Sous vide cooking at 56 °C for 6 and 12 h was characterised by lower cumulative cathepsin B and L activity, a higher degree of collagen denaturation, and a marked decrease in final yield force compared to other temperature-time combinations. The kinetics of collagen denaturation in sous vide-cooked beef brisket were also determined in this thesis, using the enthalpy of denaturation (∆H) of the second peak (Peak 2) from the thermogram generated by differential scanning calorimetry (DSC). The change in the ∆H of Peak 2 was successfully modeled using a three-protein model. The simulation of collagen denaturation using kinetic parameters obtained from the model showed a marked increase in collagen denaturation at 56 °C. A further study using precooking at 56 °C for 6 h, followed by cooking at various second-stage temperature-time combinations (60, 70, 80, and 90 °C for 0 – 20 h), showed that two-stage sous vide cooking could not reduce the total cooking time to tenderise meat compared to conventional single-temperature sous vide cooking. Based on conventional single-temperature sous vide cooking, the time required for beef brisket to reach the shear force correlated with the consumer tenderness threshold (Liang et al., 2016) was determined. It was found that at 60, 70, 80, and 90 °C, the times required to achieve the consumer tenderness threshold were 20, 26, 12, and 8 h, respectively. Although shorter times were needed to achieve the consumer tenderness threshold at 80 and 90 °C, these temperatures resulted in significantly higher cooking loss compared to 60 °C.
The following are reproduced with the publishers' permission: Figures 2.1, 2.3, 2.4, 2.5, 2.6, 2.7 and Table 2.2. Figure 2.2 is reused under a Creative Commons Attribution-ShareAlike 4.0 International (CC BY-SA 4.0) license.
Keywords: sous vide; cathepsin; collagen; meat; beef brisket; Sous-vide cooking; Meat Quality; Proteolysis; Collagen Denaturation; 300607 Food technology